Kalibrace optických souřadnicových měřicích strojů GOM ATOS - Košťák, Ondřej (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Diplomová práce obsahuje základní rozdělení 3D metod používaných pro rekonstrukci měřených objektů a druhy vzorů strukturovaného světla využívané pro 3D triangulaci. Dále se věnuje popisu konstrukce a funkcím přístrojů GOM ATOS a TRITOP. Primárně je však věnována problematice kalibrací těchto přístrojů, návrhu vhodných zkušebních těles a interní kalibrační metodiky využívané ve společnosti ŠKODA AUTO a.s. Následně práce obsahuje ověření navrženého kalibračního postupu v praxi, návrh pro stanovení nejistot kalibrace a doporučení pro praxi.

This master’s thesis contains the basic division of 3D methods which are used for reconstruction of measured objects. Furthermore the types of structured light patterns used for 3D triangulation. It also contains a description of the construction and functions of GOM ATOS and TRITOP machines. Primarily the thesis deals with the calibration of these machines, the design of suitable materials standard of size and the internal calibration methodology used by ŠKODA AUTO a.s. The text also includes verification of the proposed calibration procedure in practice, proposal for determination of calibration uncertainties and recommendations for practice.
Calibration of GOM ATOS optical coordinate measuring machines
Keywords: metrologie; kalibrace; 3D optické souřadnicové měřicí stroje; kalibrační postup; ATOS; TRITOP; zkušební tělesa; metrology; calibration; 3D optical coordinate measuring machines; calibration procedure; ATOS; TRITOP; materials standard of size